Development of green technologies in agriculture: Investment opportunities and challenges - Aigumov Aigum; Dadaev Yakub; Nurmagomedova Luiza (BIO Web of Conferences)
The article discusses the concept of a “green” economy, and also analyzes the concept of “green” bonds. The role of consumer demand as a factor in the development of the concept is assessed. Therefore, the development of green technologies in agriculture represents a necessary alternative to increase food production while minimizing the negative impact on the environment. In addition, green technologies in agriculture open up new opportunities for economic growth and development. Innovative approaches such as digitalization, the use of sensors and data analytics, and biotechnology can significantly improve the productivity and efficiency of agricultural production. This helps improve the competitiveness of agricultural enterprises and create new jobs. Thus, studying this topic allows us to identify the potential for the development of green technologies in agriculture, as well as develop strategies to overcome existing challenges and obstacles.